ANALISA PENGARUH VARIASI KUAT ARUS TERHADAP KEKUATAN TARIK SAMBUNGAN LAS SMAW DENGAN MATERIAL BAJA KARBON RENDAH DENGAN PROFIL BESI SIKU MENGGUNAKAN ELEKTRODA E6013 - MUHAMAD GILANG KRISWANDI; JATIRA; HENDRO NUGROHO (Sekolah Tinggi Teknologi Wastukancana, 2022)
Effect of welding current using SMAW welding method with E6013 electrode on the tensile strength of angle bar. Where this study aims to determine how much influence the welding current SMAW welding with electrodes E6013 diameter 2 mm on the tensile strength of the welding results. In this study, the materials used was angled iron, them V seam was made, which was welded with a current of 90 Ampere, 100 Ampere and 115 Ampere, with an E6013 electrode with a diameter 2 mm, thern tensile testing was carried out. The highest tensile strength results at 90 Ampere welding current, namely 97238 N, while the lowest occurred at 110 Ampere current, namely 1060.56 N. Current variations greatly affect the tensile strength.